Pengaruh Struktur Modal, Ukuran Perusahaan, dan Kebijakan Dividen terhadap Nilai Perusahaan pada Perusahaan Manufaktur yang Terdaftar di BEI: (Studi Kasus Perusahaan Sektor Industri Barang Konsumsi Tahun 2016-2019) - Mudjiyono, Mudjiyono; Sudarman, Sudarman; Kristiyani, Hani; Dewi, Rusiana (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2022)
The purpose of this study is to analyze the effect of capital structure, firm size, and dividend policy on firm value in manufacturing companies listed on the Indonesia Stock Exchange for the period 2016-2019. The population in this study is all company data consisting of 167 companies, the sample used is 43 companies. The research was conducted by sampling, with purposive sampling technique. The analysis technique used is multiple linear regression. Conclusion of research results: 1). Capital structure has no effect on firm value, 2). Firm size has no effect on firm value, 3). Dividend policy has a positive and significant effect on firm value.